The category of reflexivity in the Turov Gospel of the 11th century: theoretical and methodological approaches in the context of Wackernagel’s law - Serykau, Ryhor U. (Journal of the Belarusian State University. Philology, 2025)
Based on the Turov Gospel of the 11th century manuscript, the features of the written transmission of the reflexive enclitic с in the few surviving verb forms are analysed. The presence of bivalent enclitics related to two verbs in the ancient Common East Slavic text is noted. This phenomenon of archaic syntax is compared with identical phenomena in modern West Slavic languages, including Polish. Within the scope of the law of enclitic ranks developed by J. Wackernagel, the functioning of the reflexive enclitic с as part of prosodic units is characterised. The questions regarding the reasons for the agglutination of the reflexive enclitic with the verb, as well as the rearrangement of enclitics are raised. It is asserted that the first written monuments of literary and non-literary types consistently reflect the speech features of the Eastern Slavs.